2004
DOI: 10.1088/0953-8984/16/5/003
|View full text |Cite
|
Sign up to set email alerts
|

High pressure x-ray diffraction studies on nanocrystalline materials

Abstract: Application of the in situ high pressure powder diffraction technique for examination of specific structural properties of nanocrystals based on the experimental data of SiC nanocrystalline powders of 2-30 nm in diameter is presented. Limitations and capabilities of the experimental techniques themselves and methods of diffraction data elaboration applied to nanocrystals with very small dimensions (<30 nm) are discussed. It is shown that a unique value of the lattice parameter cannot be determined for such sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 64 publications
3
46
0
Order By: Relevance
“…It was shown that even simple elements under pressure can undergo surprising transformations to structures where the atoms differentiate into a host and a guest network (Nelmes et al, 1999;McMahon et al, 2000). Pressure and temperature can also be used for inducing amorphous phases of various compounds or for investigating properties of nanoparticles (Palosz et al, 2004).…”
Section: Strained Crystals Molecules and Atomsmentioning
confidence: 99%
“…It was shown that even simple elements under pressure can undergo surprising transformations to structures where the atoms differentiate into a host and a guest network (Nelmes et al, 1999;McMahon et al, 2000). Pressure and temperature can also be used for inducing amorphous phases of various compounds or for investigating properties of nanoparticles (Palosz et al, 2004).…”
Section: Strained Crystals Molecules and Atomsmentioning
confidence: 99%
“…(A.7) thatR b (h 0 , 0) does not depend on the considered Bragg reflection h 0 . Therefore, we can write 14) and the proportionality constant can be evaluated by Eq. (A.7) with ∆q = 0.…”
Section: Appendix: Error Evaluationmentioning
confidence: 99%
“…In the most complex cases, non-crystallographic structures 2,3,4,5,6,7,8,9,10,11 may occur. Surface-related deformation fields 12,13,14 are another challenge. In these extreme cases, the classical crystallographic formalism becomes quite useless.…”
Section: Introductionmentioning
confidence: 99%
“…Palosz et al [4] also used a two-phase model to interpret their diffraction data for SiC, GaN, and diamond nanoparticles. The concept of an "apparent lattice parameter" clearly indicates strong deviations of the position of Bragg peaks (especially at small angles) from the predicted crystallographic positions.…”
Section: Problem Of the Structural Diversity Of The Nanoworldmentioning
confidence: 99%